Magnetically coupled impedance-source inverters - Loh, Poh Chiang (2013)
Z-source inverters are a new class of inverters proposed with output voltage or current buck-boost ability. Despite their general attractiveness, there are some present limitations faced by existing Z-source inverters. Most of which are linked to their requirement for low modulation ratio at high input-to-output gain, and the presence of an impedance network. The former means a high dc-link voltage, which can stress the semiconductor switches unnecessarily. The latter leads to increases in cost and size, which similarly are undesirable. To lessen these concerns, an interesting approach is to use magnetically coupled transformers or inductors to raise the gain and modulation ratio simultaneously, while reducing the number of passive components needed. A study of the approach is now presented to show how various existing magnetically coupled inverters can be derived by applying a generic methodology. The same methodology is then applied to develop more magnetically coupled Z-source inverters with advantages that have not been identified in the literature. These findings have already been proven in experiments.